Antifungal potential of guava (Psidium guajava) leaves essential oil, major compounds: beta-caryophyllene and caryophyllene oxide. (14th December 2021) - Jassal, Kamalpreet; Kaushal, Sonia; Rashmi,; Rani, Reetu
Abstract: The present study investigates the antifungal potential of Psidium guajava Linn leaves essential oil and its major compounds beta-caryophyllene and caryophyllene oxide. The Clevenger apparatus was used to extract essential oil from leaves. The Gas Chromatography-Mass Spectrometry (GC-MS) analysis of leaves essential oil revealed the presence of 55 compounds with β-caryophyllene (24.97%) and caryophyllene oxide (14.92%) as major compounds were extracted from the guava leaves essential oil by column chromatography. The essential oil, caryophyllene and caryophyllene oxide were tested for their antifungal potential against Fusarium moniliforme, Rhizoctonia solani and Helminthosporium oryzae by using poison food technique. Guava leaves essential oil was most effective against Fusarium moniliforme having ED50 value of 580 μg/ml. Caryophyllene was most effective against Rhizoctonia solani and Helminthosporium oryzae having ED50 values of 450 and 510 μg/ml, respectively.